2018
DOI: 10.1017/s0714980818000375
|View full text |Cite
|
Sign up to set email alerts
|

No Place Like Home: A Systematic Review of Home Care for Older Adults in Canada

Abstract: Given Canada's aging population, the demand for home care is expected to increase significantly. To date, little is known about home care for older adults in Canada such as characteristics of home care recipients, gaps in services, or interventions designed to support home care client needs. Consequently, we conducted a systematic review of seven electronic databases for the years 2000-2016 to examine the current knowledge of home care services for Canada's older adults. This synthesis examined four main theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 59 publications
1
40
0
2
Order By: Relevance
“…In other words, as Golant (2015, p.356) advocated, we need to adopt an “it takes a village” perspective. Nevertheless, consistent with previous studies ( Johnson et al, 2018 ; Kadowaki, Wister, & Chappell, 2015 ), publicly supported long-term home care – especially for maintenance and prevention purposes, such as home support services and physiotherapy – was still unavailable for many of our participants. Our study adds further contextual evidence to Canada's need for the publicly supported long-term home care system many have advocated over the past decade ( Canadian Home Care Association, 2016 ; Gilmour, 2018 ; Kadowaki et al, 2015 ; Special Senate Committee on Aging, 2009 ; Turcotte, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In other words, as Golant (2015, p.356) advocated, we need to adopt an “it takes a village” perspective. Nevertheless, consistent with previous studies ( Johnson et al, 2018 ; Kadowaki, Wister, & Chappell, 2015 ), publicly supported long-term home care – especially for maintenance and prevention purposes, such as home support services and physiotherapy – was still unavailable for many of our participants. Our study adds further contextual evidence to Canada's need for the publicly supported long-term home care system many have advocated over the past decade ( Canadian Home Care Association, 2016 ; Gilmour, 2018 ; Kadowaki et al, 2015 ; Special Senate Committee on Aging, 2009 ; Turcotte, 2014 ).…”
Section: Discussionsupporting
confidence: 86%
“…As more and more older adults age in place, their homes and communities increasingly become locations for health and social care services (hereafter “home care”). Since long-term home care is not universally insured under the Canada Health Act, older adults who don't qualify need to resort to community agencies that often require a co-payment or privately hire help ( Armstrong, Zhu, Hirdes, & Stolee, 2015 ; Gilmour, 2018 ; Government of Ontario, 2019 ; Johnson et al, 2018 ; Lee, Barken, & Gonzales, 2018 ). According to the 2015/2016 Canadian Community Health Survey, over one-third (35.4%) of people with home care needs did not have their needs met, especially among those with home support services for maintenance of daily living ( Gilmour, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…on Open access care providers [4][5][6] and experience of informal home care providers under non-emergency health situations. 7 8 During the COVID-19 pandemic, in an attempt to reduce the surge of patients requiring hospital care, many countries have implemented epidemic control measures 9 to limit activities outside the home such as closure of nonessential services.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that institutionalization may be associated with adverse outcomes such as depression, lower quality of life, an increase in the use of medication and a rise in mortality [3][4][5][6][7][8]. Policy makers are therefore keen to foster community care and long-term care policies are shifting to allow older persons to remain in their homes for as long as possible, avoiding early nursing home admission [9][10][11][12][13][14]. According to a WHO-report (2009), an appropriate balance between care settings for older persons' care is necessary, including supported self-care and home-based services.…”
Section: Introductionmentioning
confidence: 99%